SNPs variety of 3-β-hydroxysteroid dehydrogenase 1 (HSD3B1) gene are related to prostate cancer in some Iraqi individuals - Jameel, Zahraa Isam (Reproduction and breeding, 2025)
There are numerous single nucleotide polymorphisms in the HSD3B1 gene that have been consistently associated with prostate cancer prognosis in clinical studies. HSD3B1 is a crucial gene that regulates androgens. The aim of this study was to identify any association between the HSD3B1 gene and prostate cancer susceptibility or recurrence in Iraqi patients by analyzing the effects of three specific SNPs: rs33937873 (G313A), rs6203 (C338T), and rs1047303 (1245A). The study included 100 healthy controls and 100 Iraqi patients diagnosed with incidental primary prostate cancer. The current study found that the rs33937873, which contains the heterozygote GA of G313A, is an independent risk factor for prostate cancer [odds ratio (OR) = 0.32, 95 % confidence interval (CI): 0.20–0.94, P = 0.00001]. Conversely, the C allele in rs6203 (C338T) is a significant risk factor for the development of PC (OR = 0.48, 95 % CI: 0.31–0.78, P < 0.001). Genetic testing revealed that the rs1047303 CC genotype increases the likelihood of developing PC (OR = 0.48, 95 % CI: 0.26–0.89, P = 0.02). In summary, the current study suggests that these specific polymorphisms hold considerable promise as key genetic markers for predicting which patients are at an increased risk of recurrence or mortality.